Analisis Faktor Determinan dan Efisiensi Produksi Usahatani Kelapa Dalam di Kabupaten Bengkalis - Azira, Nur (Fakultas Pertanian, Universitas Timor, 2024)
This research aims to analyze the determinant factors and production efficiency of coconut farming in Bengkalis Regency. This research was conducted in Bantan District, Bengkalis Regency, Riau Province. The total research sample was 30 respondents. The sampling method in this research uses non-probability sampling, namely a purposive sampling technique with the criteria that farmers have coconut plants with a minimum area of 1 Ha or a maximum of 10 Ha, coconut plants that are at least 15 years old and farmers who still manage coconut plantations. Determinant factors for coconut production were carried out using multiple regression analysis with the OLS (Ordinary Least Square) method. Production efficiency analysis uses the Cobb-Douglas production function model to analyze technical efficiency, allocative efficiency and economic efficiency. The research results show that the determinant factors for coconut production in Bengkalis Regency are the number of plants and labor. These two variables are significant and have a positive effect on coconut production in Bengkalis Regency. Based on the results of the production efficiency analysis of the stochastic model of the Cobb Douglas coconut production function, the use of production factors for the number of plants is not technically efficient and is not allocatively/price and economically efficient. Meanwhile, the use of labor production factors is not technically, allocatively/price and economically efficient.